The role of arts therapies in mitigating Sleep Initiation and Maintenance Disorders: a systematic review - Luo, Xuexing; Zhang, Aijia; Li, Hong; Li, Yu; Ying, Fangtian; Wang, Xiaoli; Yang, Qianxu; Zhang, Zheyu; Huang, Guanghui (Frontiers in Psychiatry, 2024)
Arts therapies, classified into passive and active modalities, are effective non-pharmacological interventions for Sleep Initiation and Maintenance Disorders (SIMDs), demonstrating notable efficacy. This systematic review aimed to evaluate both the effectiveness and ethical considerations of arts therapies for SIMDs, incorporating various randomized controlled trials (RCTs) including music therapy, meditation, and Tai Chi. Aligning with the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines, we conducted an exhaustive search across PubMed, the Cochrane Library, Web of Science, and CNKI, which culminated in the selection of 17 articles for thorough analysis. To uphold the research methodology's quality, we utilized the Joanna Briggs Institute (JBI) quality assessment criteria and employed the PICO(S) framework for data extraction specifically from RCTs. Our analysis indicates that arts therapies, whether utilized independently or in synergy, significantly enhance sleep quality. Specifically, music therapy and meditation exhibit unique benefits, while Tai Chi and Qigong demand prolonged engagement for notable improvement in sleep quality. We posit that SIMDs often stem from mental health issues such as anxiety, stress, and depression, and that arts therapies have consistently shown efficacy in addressing these mental health challenges.